Comprehensive Treatment of Curved Section Abnormal Noise for Elevated Urban Rail Transit Line - LIU Yuhang; ZHOU Changsheng; LIU jinhui; ZHOU Hualong; CHEN Sai (Chengshi guidao jiaotong yanjiu)
［Objective］ Problems of vibration and noise during the urban rail transit operation are becoming increasingly prominent. In particular, the wider impact range of elevated line noise has become a hot spot of resident complaints. Therefore, it is necessary to conduct comprehensive treatment research on the abnormal noise from urban rail transit elevated lines to alleviate the disturbance to the residents mainly caused by the "curve squeaking" noise. ［Method］ Based on the abnormal vibration and noise occurring in the curved section of an elevated metro line in Shenzhen, on-site investigation and environment noise tests are carried out respectively, corresponding treatment measures are implemented. According to the on-site test results before and after the treatment as well as under different working conditions, the noise control effects are obtained through comparative analysis of the results before and after the implementation of different measures. ［Result & Conclusion］ The rail top coating device has little influence on the overall wheel-rail noise level, but can effectively suppress the squealing noise. Grinding steel rail has significant effect on reducing wheel-rail noise, and the short-wave corrugation in the curved section is eliminated. Optimizing the train driving speed has certain effect on lessening wheel-rail noise, and can avoid the occurrence of rail side wear. Through the comprehensive application of different treatment measures, the peak value of the track-side noise is reduced by 7.4 dB(A), and the equivalent noise value is reduced by 5.9 dB(A). The peak value of the train passing noise detected at residential buildings is reduced to 0.5 dB(A) compared with the background noise, and the equivalent noise value is reduced to 0.3 dB(A). The treatment measures show a remarkable noise reduction effect in that the metro noise contributes little to the environment and the curve squealing noise no longer appears.